The wire of the worlds. (Economist, 1999)
Discusses proposals for an interplanetary Internet (IPN). How efforts to alter the Internet for space will require more reliable wireless connections and altered networking protocols; How TCP/IP, a traditional networking protocol is too chatty for space; Distances in space and their effect on communications; File transfer as another area which will require changes; Similar problems facing wireless Internet devices; The File Delivery Protocol (FDP), a modified file transfer protocol (FTP).